2020
DOI: 10.1111/jdv.16533
|View full text |Cite
|
Sign up to set email alerts
|

Acral cutaneous lesions in the time of COVID‐19

Abstract: Dear Editor, Coronavirus disease 2019 (COVID-19) has become a pandemic condition, yet little is known about its dermatologic manifestations. 1,2 We report here on peculiar (perniosis-like) skin lesions, unreported in the previous years, observed in young outpatients visited in our dermatologic unit in the last 4 weeks of COVID-19 pandemic (March-April 2020). Similar cases were referred to us in the same period by paediatricians and dermatologists from Italy and European countries. We directly observed 14 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
277
3
19

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(315 citation statements)
references
References 5 publications
14
277
3
19
Order By: Relevance
“…However, the preserved bowel sounds and the diarrheal onset of illness allowed us to wait with medical management. Varying skin lesions [7] had been described with COVID-19 infection, history of maculopapular rashes on the dorsum of feet had added the suspicion of COVID-19 in the index case.…”
Section: Discussionmentioning
confidence: 99%
“…However, the preserved bowel sounds and the diarrheal onset of illness allowed us to wait with medical management. Varying skin lesions [7] had been described with COVID-19 infection, history of maculopapular rashes on the dorsum of feet had added the suspicion of COVID-19 in the index case.…”
Section: Discussionmentioning
confidence: 99%
“…13 Of note, these PC lesions were largely unrelated to cold exposure (secondary to social isolation and stay-at-home orders) or a prior history of Raynaud's disease. 9,20,32,33,34,36 As such, these cutaneous ndings may be categorized as COVID-19-induced pseudo-chilblains rather than primary pernio disease. The majority of PC cases were associated with milder disease, resolving disease, or negative laboratory testing.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported persistent PC that required 2 to 4 weeks for complete resolution. 9 Of the dermatologic ndings that were symptomatic, the majority were pruritic (n = 295), followed by painful (n = 68) or burning (n = 24). Most patients had no new drug intake in the 2 weeks preceding rash onset.…”
Section: Id Studymentioning
confidence: 97%
See 1 more Smart Citation
“…The most common symptoms, depending on the time windows during the course of infection, are symptoms associated with respiratory diseases, such as fever, cough, sore throat, headache, chills, fatigue and myalgia, smell and taste dysfunction and gastrointestinal problems (10,11), but recently more severe cases have been associated with neurological symptoms, such as acute cerebral vascular disease, skeletal muscle injury and impaired consciousness (12). Perniosis-like skin symptoms may als be present (13,14). Risk factors for more severe cases of COVID-19 are hypertension, coronary artery disease, immunosuppression, and chronic lung disease (15).…”
Section: Introductionmentioning
confidence: 99%